Investigacion en campos de agricultores sobre frijol en Honduras - Rivera, V. (International Center for Tropical Agriculture, 1987)
The objective of the National Agricultural Research Department in Honduras is to coordinate, organize, and supervise research activities in different areas. This technological system includes 4 stages: diagnosis, planning, expt., and transference. The most commonly used improved var. are Zamorano, Danli 47, and Desarrural. Recommendations include two weedings during the 1st 30 days after planting, fertilization with 10 and 30 kg P and N/ha, resp. applied at planting, plant density of 200,000 and 300,000 plants/ha for the 1st and 2nd plantings of the yr., resp., and slug control with cultural practices and poisoned baits. The program also evaluates ecotypes from CIAT with desirable agronomic and commercial characteristics, and resistant to the main diseases in the country. (CIAT)